Nonvalvular atrial fibrillation: a study of epidemiology, demography and clinicoetiological profile in Central India - Jain, Mayank; Kiyawat, Priyanka (International Journal of Advances in Medicine, 2018)
Background: Atrial fibrillation (AF) is the most common sustained disorder of cardiac rhythm. To study the epidemiology, demography and clinicoetiological profile of nonvalvular atrial fibrillation, such studies are sparse in India. Methods: One hundred sixty-five patients of nonvalvular atrial fibrillation were enrolled prospectively in the study during the period February 2017 to May 2018. Patients with an electrocardiographic documentation of atrial fibrillation, either chronic or paroxysmal were enrolled in the study. Patients underwent thorough physical examination, routine laboratory testing, and other relevant investigations to assess the underlying etiology. Baseline characteristics of all the patients’ viz. type of AF, primary etiological diagnosis, and baseline clinical parameters were noted. Statistical analysis was done using percentage analysis. Results: A total of 165 patients were enrolled in the study. The vast majority of patients were elderly; with the majority being in the 56-65years age group (45.45%). AF was more common in men (56.3%). Systemic hypertension was the most common etiological association (80%). Conclusions: Present study found that advanced age and male gender are significant risk factors for AF. Systemic hypertension is the most common etiological association with nonvalvular AF.